2021
DOI: 10.1016/j.onehlt.2021.100247
|View full text |Cite
|
Sign up to set email alerts
|

Risk of SARS-CoV-2 transmission from humans to bats – An Australian assessment

Abstract: SARS-CoV-2, the cause of COVID-19, infected over 100 million people globally by February 2021. Reverse zoonotic transmission of SARS-CoV-2 from humans to other species has been documented in pet cats and dogs, big cats and gorillas in zoos, and farmed mink. As SARS-CoV-2 is closely related to known bat viruses, assessment of the potential risk of transmission of the virus from humans to bats, and its subsequent impacts on conservation and public health, is warranted. A qualitative risk assessment was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…For example, North American bats are threatened by an emerging disease, white-nose syndrome, 89 which has documented synzootic interactions with other bat coronaviruses; 90 at least seven North American bat species that can be infected by the fungal pathogen ( Eptesicus fuscus, Myotis ciliolabrum, Myotis lucifugus, Myotis septentrionalis, Myotis velifer, Myotis volans , and Tadarida brasiliensis ) are among the 412 bat species that we predicted could be undiscovered betacoronavirus hosts. Although our predictions do not imply bat susceptibility to SARS-CoV-2 specifically (and experimental infections of E fuscus have been unsuccessful 91 ), efforts to minimise the risks of SARS-CoV-2 spillback into novel bat reservoirs, 92 , 93 , 94 , 95 , 96 as well as to understand the dynamics of other bat coronaviruses, will both reduce zoonotic risk and help to understand and counteract disease-related population declines. Similarly, conservationists have expressed concern that the negative framing of bats as the source of SARS-CoV-2 has affected public and governmental attitudes toward bat conservation; 97 this can fuel negative responses, including indiscriminate culling (ie, the reduction of populations by slaughter), which has already occurred in response to COVID-19 even outside of Asia (where a spillover probably occurred).…”
Section: Discussionmentioning
confidence: 74%
“…For example, North American bats are threatened by an emerging disease, white-nose syndrome, 89 which has documented synzootic interactions with other bat coronaviruses; 90 at least seven North American bat species that can be infected by the fungal pathogen ( Eptesicus fuscus, Myotis ciliolabrum, Myotis lucifugus, Myotis septentrionalis, Myotis velifer, Myotis volans , and Tadarida brasiliensis ) are among the 412 bat species that we predicted could be undiscovered betacoronavirus hosts. Although our predictions do not imply bat susceptibility to SARS-CoV-2 specifically (and experimental infections of E fuscus have been unsuccessful 91 ), efforts to minimise the risks of SARS-CoV-2 spillback into novel bat reservoirs, 92 , 93 , 94 , 95 , 96 as well as to understand the dynamics of other bat coronaviruses, will both reduce zoonotic risk and help to understand and counteract disease-related population declines. Similarly, conservationists have expressed concern that the negative framing of bats as the source of SARS-CoV-2 has affected public and governmental attitudes toward bat conservation; 97 this can fuel negative responses, including indiscriminate culling (ie, the reduction of populations by slaughter), which has already occurred in response to COVID-19 even outside of Asia (where a spillover probably occurred).…”
Section: Discussionmentioning
confidence: 74%
“…If this happens, it will be very difficult to eradicate the virus. Moreover, vaccination of humans and pets will not be successful also [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that cat fleas, Ctenocephalides felis , might act as biological and/or mechanical vectors, as coronavirus‐derived RNA and cell receptor ACE RNA/proteins were identified in cat fleas. 212 However, current evidence suggests that pets are probably “dead‐end”‐hosts with small risk of transmission to humans. Still, pet owners are concerned: 60% of U.S. veterinarians encountered owners that were worried about their pets having COVID‐19.…”
Section: Origin and Transmissionmentioning
confidence: 99%